Sibling Issues in Therapy Research and Practice with Children, Adolescents and Adults - Milevsky, Avidan (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Incorporating the latest research and clinical work in family dynamics, this book examines multiple angles of integrating sibling issues, which underlie issues at the core of many clinical difficulties presented by adult clients, in therapy to improve adulthood emotional and psychological well-being.